2020
DOI: 10.1055/s-0040-1701441
|View full text |Cite
|
Sign up to set email alerts
|

Navigation Improves the Survival Rate of Mobile-Bearing Total Knee Arthroplasty by Severe Preoperative Coronal Deformity: A Propensity Matched Case–Control Comparative Study

Abstract: The primary hypothesis of this study was that the survival rate over 10 years of total knee arthroplasties (TKAs) implanted with a navigation system was superior to that of TKAs implanted with a conventional technique. The secondary hypothesis was that the severity of the initial coronal deformity had a negative influence on the survival rate. A national, multicentric, retrospective study was performed in France, including eight university or private centers with high volumes in knee surgery. Cases operated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The cost-effectiveness of TA-TKA systems has been a controversial topic in orthopaedic surgery. Previous studies aiming to evaluate the net benefit or cost of implementing TA-TKA systems have not demonstrated improvements in implant survivorship in the general population of patients undergoing TKA [13, 15, 18, 26-28, 31, 32, 39, 40, 62]. The simulation results presented above suggest that technology assistance cannot generally be considered to be cost effective for application across the board in a general clinical population.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The cost-effectiveness of TA-TKA systems has been a controversial topic in orthopaedic surgery. Previous studies aiming to evaluate the net benefit or cost of implementing TA-TKA systems have not demonstrated improvements in implant survivorship in the general population of patients undergoing TKA [13, 15, 18, 26-28, 31, 32, 39, 40, 62]. The simulation results presented above suggest that technology assistance cannot generally be considered to be cost effective for application across the board in a general clinical population.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have argued that many revision procedures (approximately 70% [1, 11, 48]) are related to mechanical aspects of the procedure that are under the surgeon’s control, such as implant alignment. To reduce outliers in making bone cuts and placing implants, robotic, navigated and patient-specific instrumentation (PSI) systems have been introduced with the goal of improving the precision of bone cuts and implant alignment [13, 15, 18, 26-28, 31, 32, 39, 41, 62].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, leaving the femoral component in excessive varus or valgus alignment leads to elevated revision rates [26]. To reduce such outliers, robotic and navigated TKA procedures (collectively referred to herein as technology-assisted TKA [TA-TKA]) have been introduced to improve the precision of bone cuts and implant alignment [4, 9, 11, 12, 14, 18-25, 28-31, 33, 35, 36]. Although these innovations in surgical navigation have improved the accuracy of implant placement, most comparative outcome studies have not demonstrated clear reductions in revision rates [9, 11, 12, 14, 18-25, 28-31, 33, 35, 36].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce such outliers, robotic and navigated TKA procedures (collectively referred to herein as technology-assisted TKA [TA-TKA]) have been introduced to improve the precision of bone cuts and implant alignment [4, 9, 11, 12, 14, 18-25, 28-31, 33, 35, 36]. Although these innovations in surgical navigation have improved the accuracy of implant placement, most comparative outcome studies have not demonstrated clear reductions in revision rates [9, 11, 12, 14, 18-25, 28-31, 33, 35, 36]. One retrospective trial [4] reported a significant difference but had a high loss to follow-up rate (56%) and no controls for preoperative patient demographics, with statistically significant differences in age at the index surgery and BMI between the conventional group and the navigated group, likely resulting in a higher risk of revision for the conventional group simply based on these patient-specific factors (younger age at surgery and increased BMI [5, 7]).…”
Section: Introductionmentioning
confidence: 99%